Penerjemahan Teks Suci: Analisis Ketepatan Terjemahan Istilah Kecendekiaan Dalam Alquran dan Terjemahnya - Syihabuddin, Syihabuddin (Sunan Kalijaga State Islamic University Yogyakarta, 2016)
This research aims to determine the accuracy of the translation of scholarly terms, namely ulū al-albāb, ulū al-‘ilm, ulū al-nuhā, and ulū al-abṣār in the holy scripture of Alquran and its translation, published by the Department of Religious Affairs of the Republic of Indonesia. In addition,the factors influencing the accuracy of the translation is analysed. To meet the aim, the data on scholarly terms and their translations were collected using Q-soft ELRA software version 1.0.0. The data were then analysed semantically by comparing both the lexical and contextual meanings in their source and target languages. Based on the analysis and discussion, it is found that the terms ulū al-albāb, ulū al-‘ilm, ulu an-nuhā, and ulū al-abṣār are translated in various ways. Ulū al-albāb and ulū an-nuha are translated quite accurately, ulū al-‘ilm accurately, and ulū al-abṣār rather inaccurately. The levels of accuracy are influenced by the translation techniques that is used, cultural differences, and inaccuracy in understanding the lexical meanings. The four terms describe the semantic relations from the most specific to the most general, namely ulū al-albāb, ulū al-nuhā, ulū al-abṣār, and ulū al-‘ilm respectively.